Enhanced arsenate reduction by a CDC25-like tyrosine phosphatase explains increased phytochelatin accumulation in arsenate-tolerant Holcus lanatus - Bleeker, Petra M; Hakvoort, Henk W.J; Bliek, Mattijs; Souer, Erik; Schat, Henk (The Plant journal : for cell and molecular biology, 2006)
Decreased arsenate [As(V)] uptake is the major mechanism of naturally selected As(V) hypertolerance in plants. However, As(V)-hypertolerant ecotypes also show enhanced rates of phytochelatin (PC) accumulation, suggesting that improved sequestration might additionally contribute to the hypertolerance phenotype. Here, we show that enhanced PC-based sequestration in As(V)-hypertolerant Holcus lanatus is not due to an enhanced capacity for PC synthesis as such, but to increased As(V) reductase activity. Vacuolar transport of arsenite-thiol complexes was equal in both ecotypes. Based on homology with the yeast As(V) reductase, Acr2p, we identified a Cdc25-like plant candidate, HlAsr, and confirmed the As(V) reductase activity of both HlAsr and the homologous protein from Arabidopsis thaliana. The gene appeared to be As(V)-inducible and its expression was enhanced in the As(V)-hypertolerant H. lanatus ecotype, compared with the non-tolerant ecotype. Homologous ectopic overexpression of the AtASR cDNA in A. thaliana produced a dual phenotype. It improved tolerance to mildly toxic levels of As(V) exposure, but caused hypersensitivity to more toxic levels. Arabidopsis asr T-DNA mutants showed increased As(V) sensitivity at low exposure levels and enhanced arsenic retention in the root. It is argued that, next to decreased uptake, enhanced expression of HlASR might act as an additional determinant of As(V) hypertolerance and As transport in H. lanatus.